IFPRI Strategy 2013–2018: Food policy research in a time of unprecedented challenges - International Food Policy Research Institute (International Food Policy Research Institute, 2013)
The global food policy landscape is rapidly changing. Food prices are increasingly volatile. Rising incomes, urbanization, and changing dietary preferences are transforming food supply chains. Climate change and weather-related shocks are escalating. And the growing scarcity of water, energy, and land means that in order to feed a growing global population, agricultural and food systems must do more with less. As the world faces unprecedented challenges, IFPRI has developed a new strategy to address the most critical food policy issues.